Menteri Agama Dalam Bingkai Media Di Masa Pandemi Covid-19: Analisis Framing Robert Entman Mengenai Wacana Menteri Agama dalam Penanganan Covid-19 Pada Kompas.Com dan Detik.Com - Jamiluddin Nur; Irdan Hildansyah (Alif Lam: Journal of Islamic Studies and Humanities, 2021)
This study aims to see the framing carried out by the online media Kompas.com and Detik.com against the Minister of Religion of the Republic of Indonesia, Yaqut Cholil. This study uses a qualitative research approach. Thus, this study looks at the meaning of individual or group problems in human life. This study uses Robert Entman's analytical model to identify Kompas.com and Detik.com framing. data collection is done by making observations via the internet. The researcher saw news about the Minister of Religion in the period of June and July. After making observations, the researchers collected and documented the data from the observations. The researcher then selected news relevant to the Minister of Religion and the handling of the Covid-19 virus in Indonesia. The next researcher analyzed the relevant news using Robert Entman's framing analysis model. The results of this study indicate that Kompas.com frames the Minister of Religion as a person who has the capacity to invite all religious leaders and major mass organizations to participate in preventing the transmission of COVID-19. The Minister of Religion is also framed as a person who has the power to make relevant regulations to prevent the spread of the virus. Meanwhile, Detik.com frames the Minister of Religion to be more concerned with technical matters, such as meat distribution and slaughtering sacrificial meat. It does not appear that the Minister of Religion has the power to make substantial policies. The power of the Minister of Religion is shown to be limited to technical prohibitions. The analysis of Entman's model is not sufficient to explain the reality of media holistically. Not all news provides moral judgment and problem solving. This limitation makes this study need other analytical tools to explain the phenomenon, although it is not very well established. Further in-depth research with other analytical tools is needed to get a more comprehensive picture of framing.